From Policy to Practice: Implementing Corporate Social Responsibility in Environmental Development Programs - Situmorang, Puji Erlin; Sihombing, Tunggul (Jurnal Kebijakan Publik, 2025)
This study aims to determine and interpret the Implementation of Corporate Social Responsibility (CSR) Policy of PTPN IV Kebun Pabatu Community Development Program in Kedai Damar Village, Tebing Tinggi District. The research method used in this research is qualitative research with a descriptive approach. Data collection techniques were carried out by means of observation, interviews, and documentation conducted at the Office of PT Nusantara IV Plantation Pabatu and Kedai Damar Village, Tebing Tinggi District. The data obtained were analyzed qualitatively with the approach of policy implementation theory proposed by Edwards III, including communication, resources, disposition, and bureaucratic structure. The results of this study indicate that the implementation of Corporate Social Responsibility (CSR) environmental development program in PTPN IV Kebun Pabatu from the aspect of communication is not good enough marked by consistency in the delivery of information that is only done when there are activities only. The resource aspect is good enough. The aspect of disposition that is not good enough is marked by the weak commitment and responsibility of the company in supervising the implementation of the program that has been carried out so that it has not run optimally. This can be seen from the road that has been repaired through the assistance of the Corporate Social Responsibility (CSR) environmental development program, which has been damaged again in a relatively short period of two years. The bureaucratic structure has been carried out quite well.